Avaliação do impacto de ambientes gamificados no processo de ensino-aprendizagem da lógica de programação de computadores: uma comparação entre elementos monousuário e multiusuários - RIBEIRO, Fabrício de Sousa (Universidade Federal do Pará, 2020)
In Technology courses that have in their curriculum matrix disciplines related to software development (such as Fundamentals of Programming), students have learning difficulties in the development of algorithms. Consequently, a methodology that is beyond the traditional teaching-learning methods is necessary, as students need different strategies that can increase their engagement. In this sense, the use of gamification techniques is a promising alternative to the positive results of their application in various areas, including education. In this scenario, digital games stand out. These can be classified into single and multiuser games. Given the above, this paper aims to compare the impact of the use of gamified environments in the teaching-learning process of computer programming logic between single-user and multi-user context. The study procedures were divided into three moments: systematic literature review, preparation of the experimental environment and performance of the experiments. The selected environment corresponds to the Code Combat game, with a modified version to integrate the multiuser features. The experiments were carried out with 38 students from a technical course integrated with high school. The data suggest an increased engagement of students who made use of the gamified environment that uses multiuser resources, but statistically, no significant learning differences were identified between the use of both types of resources.